Tradisi Peringatan Rebb’e Di Perkumpulan Keluarga Madura, Kota Sorong - roihan, thoriq; Masseni, H; syahrul (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2024)
This research uses qualitative research methods with a phenomenological study approach and a da'wah approach. Focused on the local community in the city of Sorong and introducing what a rebbe tradition is, and whether it has a correlation and whether there is an acculturation value in it The research subject was aimed at the Madurese community in the city of Sorong and introduced it to the local community. The data collection techniques used were observation, interviews and documentation. While the data validity technique uses data triangulation, the data analysis technique used is a qualitative descriptive approach. The results of this research show that, as follows: 1) The Rebbe's tradition is a positive activity that is in accordance with the Shari'a in the process of sending prayers to the deceased, as well as getting to know more in the process of the Rebbe's tradition. 2) The Rebbe Tradition is an ancient tradition in Madura, and how to attract a preaching message contained in the rebbe tradition process 3) Collaboration of a tradition that occurs in the city of Sorong, the Rebbe tradition is collaborated with a local tradition which then has the value of acculturation inside it